Children's mental health and recreation: Limited evidence for associations with screen use. (8th May 2020) - Kostyrka‐Allchorne, Katarzyna; Cooper, Nicholas R.; Simpson, Andrew; Sonuga‐Barke, Edmund J. S.
Abstract: Aim: This study examined the direct and indirect associations between childhood psychopathology symptoms, screen use, media multitasking and participation in non‐digital recreation. Methods: Psychopathology symptoms, media use, media multitasking, participation in sports, social clubs and reading/games were reported by 520 parents about their 3‐ to 11‐year‐old children. The data were analysed using structural equation modelling. Results: There were bidirectional negative associations between sports participation and emotional problems ( β = −0.16, P < .001 and β = −0.15, P < .001); attention deficit hyperactivity disorder (ADHD) symptoms were associated with reduced reading/games ( β = −0.14, P = .004). A bidirectional positive association was found between media use and conduct problems ( β = 0.10, P = .015 and β = 0.14, P = .015). Increased media multitasking was indirectly associated with elevated symptoms of ADHD via a reduction in reading/games ( β = 0.10, P = .026). However, there was no evidence that screen use mediated the associations between psychopathology symptoms and non‐digital recreation. Conclusion: Depending on the specific psychological difficulties, children are either less likely to participate in non‐digital recreation or are more likely to use screen media or multitask with media. Interventions for children, who experience emotional or behavioural difficulties, are needed to improve participation in non‐digital recreation.